PENGARUH APLIKASI BACILLUS SUBTILIS DAN BOKASI ECENG GONDOK TERHADAP PERTUMBUHAN DAN HASIL PADI SIAM LANTIK - Noraida Hayati; Raihani Wahdah; Salamiah Salamiah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
This study aims to analyze the interaction of Bacillus subtilis and water hyacinth bokashi on the growth and yield of the Siam Lantik and to analyze the best combination of Bacillus subtilis and the water hyacinth bokashi on the growth and yield of Siam Lantik. This study was conducted using a factorial randomized block design. The first factor was the concentration of Bacillus subtilis (E), which consisted of 3 (three) levels, namely e1: 16 L ha-1, e2: 32 L ha-1, and e3: 48 L ha-1. The second factor was the dose of water hyacinth bokashi (G), which consisted of 5 (five) levels, namely g1: 10 t ha-1, g2: 15 t ha-1, g3: 20 t ha-1, g4: 25 t ha-1, and g5: 30 t ha-1. The analysis of variance showed the effect of the interaction for the number of tillers per clump aged 4 and 5 WAP. The results showed that the Bacillus subtilis treatment significantly affected plant height at 4 WAP and the weight of filled grain per panicle. In comparison, applying water hyacinth bokashi significantly affects plant height at 3 WAP.